2014
DOI: 10.1021/jp500609h
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Induced Phase Transitions in Lead-Free Bi0.5Na0.5TiO3 Based Ceramics

Abstract: Lithium-substituted 0.95[0.94(Bi 0.5 Na (0.5−x) Li x )TiO 3 −0.06BaTiO 3 ]− 0.05CaTiO 3 materials include the polar rhombohedral R3c and the weakly polar tetragonal P4bm phases. On increasing lithium content, the (R3c/P4bm) phase ratio decreased, while the rhombohedral and tetragonal lattice distortions remained the same. The temperature corresponding to the shoulder in the dielectric permittivity shows no clear shift with respect to lithium substitution because of the rhombohedral distortion remaining constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
70
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(89 citation statements)
references
References 34 publications
17
70
2
Order By: Relevance
“…4,25 A negative ECE has also been observed by indirect ECE measurements on NBT, 9 was attributed to the presence of a field-induced phase transition from tetragonal AFE to a more entropic tetragonal FE phase. The negative effect in NBT-18KBT is most likely also due to the presence of a weakly polar phase with different dipolar directions at low applied fields as reported by Viola et al 26 Similar to NBT-BT, 27,28 unpoled ceramics with compositions near the MPB of NBT-KBT show a mixture of R3c and P4bm polar nano-regions. 29 The tetragonal P4bm phase is a weakly polar relaxor ferrielectric with antiparallel cation displacements along the polar axis.…”
supporting
confidence: 58%
“…4,25 A negative ECE has also been observed by indirect ECE measurements on NBT, 9 was attributed to the presence of a field-induced phase transition from tetragonal AFE to a more entropic tetragonal FE phase. The negative effect in NBT-18KBT is most likely also due to the presence of a weakly polar phase with different dipolar directions at low applied fields as reported by Viola et al 26 Similar to NBT-BT, 27,28 unpoled ceramics with compositions near the MPB of NBT-KBT show a mixture of R3c and P4bm polar nano-regions. 29 The tetragonal P4bm phase is a weakly polar relaxor ferrielectric with antiparallel cation displacements along the polar axis.…”
supporting
confidence: 58%
“…Typical ferroelectric behaviour was observed for NBT-0.01KN, with the peaks in the J-E curves being produced by polarization switching at the coercive field. 29 However, the remanent polarization value for this composition (~0.08 C m -2 ) was relatively low, indicating that only a poorly saturated state was obtained due to a high coercive field (> 4 kV mm -1 ). In contrast, the NBT-0.03KN ceramic exhibited more complete ferroelectric switching behaviour at room temperature with a remanent polarization of approximately 0.24 C m -2 ,…”
Section: (C) (D) (A) (B)mentioning
confidence: 75%
“…The transition in NBT-0.05KN was found to be partially reversible, giving rise to two peaks in the J-E curve which represent the forward electric field (E F ) and backward electric field (E B ) to trigger the switching. 29 Therefore, it is concluded that at room temperature an irreversible transformation from weak-polar to the ferroelectric-ordered phase occurs for x=0.01 and x=0.03, with the process being partially reversible for x=0. Selected regions of the x-ray diffraction patterns obtained for both unpoled and poled ceramic powders having a range of different compositions are presented in Figure 5 (a) and (b) respectively.…”
Section: (C) (D) (A) (B)mentioning
confidence: 98%
“…36 However, the addition of small quantities of orthorhombic KNN seems to disrupt the long range ferroelectric order and induces altered characteristic in the material system. 27,28,36 Tan et al reported that addition of KNN in increasing quantities was also responsible for reduced depolarization temperature and increasing non-ferroelectric characteristics of the original BNT-BT composition. 44 It was observed that 0.91(Bi 0.5 Na 0.5 )TiO 3 -0.07BaTiO 3 -0.02(K 0.5 Na 0.5 )NbO 3 possess largely pseudo-cubic structure in contrast to 0.94(Bi 0.5 Na 0.5 )TiO 3 -0.05BaTiO 3 -0.01(K 0.5 Na 0.5 )NbO 3 which was characterized by a rhombohedral R3c symmetry and displays largely ferroelectric behavior.…”
Section: A Materialsmentioning
confidence: 99%
“…However, recent reports reveal it to be a relaxor ferroelectric. [25][26][27][28] Even though the nature of ferroelectric response in BNT-BT-KNN is yet debatable, the energy storage characteristics are essentially derived from P-E hysteresis analysis. Since the P-E analysis of BNT-BT-KNN exhibits a pinched loop native to anti-ferroelectric compositions, an assumption based on anti-ferroelectric characteristics is expected to provide accurate description.…”
Section: Introductionmentioning
confidence: 99%